احتياجات مجتمع مصر ما بعد ثورة 25 يناير 2011 في قصة هم وهؤلاء لأحمد فرج (دراسة النقد الأدبي) - Imam Wicaksono; Karlina Maizida (IAIN Salatiga, 2019)
This study aimed at revealing the needs of Egyptian people after the 2011 revolution and how they could meet their needs amidst increasingly difficult economic conditions. This was literary study by analyzing Arabic literary works. It used Abraham Harold Maslow's humanistic psychology theory which holds that human needs are described in a hierarchy. To meet the needs at the top level, the needs at the previous level must first be satisfied. In the context of Egyptian society, they have freedom of expression as the highest hierarchical need of self-actualization. This becomes very interesting when told in the material object of research: people have freedom of expression but they still feel hungry and insecure, the most basic need for humans. The results showed that after the fall of Husni Mubarak, Egypt underwent a change in the political field that the Egyptian people get freedom of expression as citizens. Unfortunately, the progress of democracy was not followed by the progress of other fields such as social and economic fields. After leadership change in 2011, life was increasingly difficult with rising prices for basic necessities and Egyptian society was increasingly difficult to find work. This made them far from a decent life such as owning a house, vehicle or marriage.